Сlassification of costs and calculation methods as directions of cost management of companies - Dong Hai; Дун Хай (Запоріжжя : Видавничий дім «Гельветика», 2025)
EN: The article examines the issue of cost classification as an important tool of the cost management system in companies. It is established that the classification of costs involves their division into separate types and allows establishing appropriate mechanisms for generating information on costs and making optimal management decisions regarding the financial and economic activities of a company. It is substantiated that grouping costs by different classification features reflects the content of the company's costs in various aspects of its activities and expands the management functions, taking into account the specific conditions of the production process. It has been found that cost management is also carried out through the use of various methods of costing products (works, services). It is determined that the purpose of forming different costs is to collect and process cost data for making management decisions at the time when their use will be most effective. It is found that the use of different methods of cost accounting depends on the objects of accounting, the completeness of the inclusion of costs in the cost of production and its managerial interpretation. /// UA: У статті проаналізовано напрямки класифікації витрат за способом включення до собівартості, по відношенню до обсягу виробництва та за значимістю для компанії. Серед варіантів різних методів калькулювання (повнота включення витрат до собівартості, фактичної та нормативної собівартості, об’єктом обліку витрат) обґрунтовано обрання кожного з них виходячи зі змісту методу та специфіки діяльності компанії.
Класифікація витрат та методів калькулювання як напрями управління витратами компаній
Keywords: direct and indirect costs; variable and fixed costs; relevant and irrelevant costs; direct costing; absorption costing; ABC calculation method; прямі та непрямі витрати; змінні та постійні витрати; релевантні та нерелевантні витрати; директ-костинг; абзорпшен-костинг; АВС-метод калькулювання